Functional outcomes in children and young people with dyskinetic cerebral palsy. (8th March 2017) - Monbaliu, Elegast; De La Peña, Mary‐Grace; Ortibus, Els; Molenaers, Guy; Deklerck, Jan; Feys, Hilde
Abstract : Aim: This cross‐sectional study aimed to map the functional profile of individuals with dyskinetic cerebral palsy (CP), to determine interrelationships between the functional classification systems, and to investigate the relationship of functional abilities with dystonia and choreoathetosis severity. Methods: Fifty‐five children (<15y) and young people (15–22y) (30 males, 25 females; mean age 14y 6mo, standard deviation 4y 1mo) with dyskinetic CP were assessed using the Gross Motor Function Classification System (GMFCS), Manual Ability Classification System (MACS), Communication Function Classification System (CFCS), Eating and Drinking Ability Classification System (EDACS), and Viking Speech Scale (VSS), as well as the Dyskinesia Impairment Scale. Results: Over 50 per cent of the participants exhibited the highest limitation levels in GMFCS, MACS, and VSS. Better functional abilities were seen in EDACS and CFCS. Moderate to excellent interrelationship was found among the classification scales. All scales had significant correlation ( r s =0.65 – 0.81) with dystonia severity except for CFCS in the young people group. Finally, only MACS ( r s =0.40) and EDACS ( r s =0.55) in the young people group demonstrated significant correlation with choreoathetosis severity. Interpretation: The need for inclusion of speech, eating, and drinking in the functional assessment of dyskinetic CP is highlighted. The study further supports the strategy of managing dystonia in particular at a younger age followed by choreoathetosis in a later stage. What this paper adds: Dystonia is significantly related with all classifications, except the Communication Function Classification System (CFCS). Eating and Drinking Ability Classification System (EDACS) and Viking Speech Scale are significantly related with Gross Motor Function Classification System (GMFCS), Manual Ability Classification System (MACS), and CFCS. No significant relationship between choreoathetosis and classification scales at young age. Higher relationship between choreoathetosis and MACS and EDACS at older age. This article is commented on by Pueyo on page570 of this issue. Video Podcast:https://youtu.be/fr8UOj3tdk4